LAS TECNICAS ACTIVAS DE APRENDIZAJE Y SU INCIDENCIA EN EL PROCESO ENSEÑANZA APRENDIZAJE EN LOS EDUCANDOS DEL CUARTO AL SETIMO AÑO DE EDUCACION BASICA DE LA ESCUELA DE APLICACIÓN PEDAGOGICA DEL INSTITUTO PEDAGOGICO ''LOS RIOS'', DE LA PARROQUIA PIMOCHA, CANTON BABAHOPYO PROVINCIA DE LOS RIOS, PERIODO LECTIVO 2004. - PATRICIA CAMACHO ABRIL (2004)
ACTIVE LEARNING TECHNIQUES AND THEIR IMPACT ON THE TEACHING-LEARNING PROCESS IN STUDENTS FROM THE FOURTH TO SEVENTH YEAR OF BASIC EDUCATION OF THE SCHOOL OF PEDAGOGICAL APPLICATION OF THE ''LOS RIOS'' PEDAGOGICAL INSTITUTE, OF THE PIMOCHA PARISH, CANTON BABAHOOPYO PROVINCE OF LOS RIOS, SCHOOL PERIOD 2004.